Answer:
Step-by-step explanation:
Vertex A of the triangle ABC when rotated by 90° counterclockwise about the origin,
Rule to be followed,
A(x, y) → P(-y, x)
Therefore, A(1, 1) → P(-1, 1)
Similarly, B(3, 2) → Q(-2, 3)
C(2, 5) → R(-5, 2)
Triangle given in second quadrant will be the triangle PQR.
If the point P of triangle PQR is reflected across a line y = x,
Rule to be followed,
P(x, y) → X(y, x)
P(-1, 1) → X(1, -1)
Similarly, Q(-2, 3) → Y(3, -2)
R(-5, 2) → Z(2, -5)
Therefore, triangle given in fourth quadrant is triangle XYZ.
Hi there!
Since 1 - 5/6 = 1/6, 1/6 of the pizza is left.
Hope this helps!
X(x+18) <= 175
<span>x^2+18x-175 <= 0 </span>
<span>(x+25)(x-7) <= 0 </span>
<span>So, -25 <= x <= 7 </span>
<span>Or, for real-world tables, </span>